The D∗Dπ and B∗Bπ couplings from light-cone sum rules - Khodjamirian, Alexander; Melić, Blaženka; Wang, Yu-Ming; Wei, Yan-Bing (The journal of high energy physics, 2021)
A bstract We revisit the calculation of the strong couplings D ∗ Dπ and B ∗ Bπ from the QCD light-cone sum rules using the pion light-cone distribution amplitudes. The accuracy of the correlation function, calculated from the operator product expansion near the light-cone, is upgraded by taking into account the gluon radiative corrections to the twist-3 terms. The double spectral density of the correlation function, including the twist-2, 3 terms at O α s and the twist-4 LO terms, is presented in an analytical form for the first time. This form allows us to use various versions of the quark-hadron duality regions in the double dispersion relation underlying the sum rules. We predict g D ∗ Dπ = 14.1 − 1.2 + 1.3 and g B ∗ Bπ = 30.0 − 2.4 + 2.6 when the decay constants of heavy mesons entering the light-cone sum rule are taken from lattice QCD results. We compare our results with the experimental value for the charmed meson coupling and with the lattice QCD calculations.